Settlement of Community Land Disputes Around The Dam Through Legal Approach and Local Wisdom - Nirwan Junus; Nurul Fazri Elfikri; Karlin Z. Mamu; Reynaldi B. Ndeo (Institut Agama Islam Negeri Curup, 2025)
The construction of Bulango Ulu Dam in Gorontalo province is a national strategic project aimed at raw water supply, irrigation, and flood control. However, in the process of construction, land rights disputes arose between the government and local communities. This dispute is triggered by differences in perceptions about the value of compensation, as well as the limited information received by the community regarding the status and boundaries of land affected by development, so that a comprehensive study of the appropriate dispute resolution mechanism is needed. This study aims to examine the concept of land dispute resolution in general and analyze the process of land dispute resolution that occurs around the construction of the Bulango Ulu Dam. This study uses the method of Empirical Legal Research (socio-legal research), which is a method that combines normative study of legislation with factual data obtained in the field. Data collection was carried out through direct observation at affected dam construction sites, in-depth interviews with land owners or tenants, as well as agencies related to the land acquisition process, then analyzed in a descriptive qualitative manner. The results showed that the concept of land dispute resolution emphasizes a multidimensional approach that integrates legal certainty, community participation, and social justice principles. Settlement is carried out through comprehensive legal mechanisms, both non-litigation such as mediation and deliberation, as well as litigation through courts or arbitration, with the strategic role of the National Land Agency (BPN) in the prevention and handling of cases. In this Bulango Ulu Dam conflict, the settlement steps include inventory and identification of land by BPN to determine the legal status and basis for compensation, socialization to explain the rights, obligations, and procedures for land acquisition, as well as deliberation to reach a fair agreement and accepted by all parties. This deliberative approach reflects the values of local wisdom such as togetherness, consensus, and respect for the rights of indigenous peoples, so as to provide a more participatory solution, and accepted by the community.